(3QaY GdEUQ Yf bVGI eUQs - (3CMeO Hf Ydj Hf eMeO Hf MLQ GdTGaYj GdcfGfj GdYSbdGfj, TgGH GdOjf CHh GdaVd, GHf MLQ, J (B852 (3g` s ((3CMeO Hf CHj GdTjN Ydi GdSHcj s)
(3ChdgG (B:s
(3CeG HYO , abO hbaJ Ydi QLR ai PcQ ef hdi GdbVGA HGdOjGQ GdeUQjI , ef fXe GdCOjH GdeTghQ TeS GdOjf Hf OGfjGd GdcMGd s
(3BNQgG (B:s
(3hcGf GdebQQ GdTgGOI ajeG jJYGdb HGdCjJGe hGdhUGjG YTQI CfaS hGddg CYde HGdUhGH s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B70 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B75 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B204 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs